Uma voz para a América Latina? A elaboração discursiva da vida de Mercedes Sosa em documentários biográficos - Souza, Nathan Bastos de (2021)
Mercedes Sosa (1935-2009) was an Argentine singer who was fundamental in the development of Latin American music with a social perspective and her political activity raised the militant content of the songs. In this thesis we study the biographical discourse about her in three documentaries "Mercedes Sosa - Como un pájaro libre", directed by Ricardo Wüllicher, 1983, "Mercedes Sosa - ¿Será posible el sur?" directed by Stefan Paul, 1985, and “Mercedes Sosa, la voz de Latinoamérica”, by Rodrigo Vila, 2013. In this sense, the research is guided by a question: how is Mercedes Sosa's life elaborated discursively in the biographical documentaries and what are the elements considered valid in her profile to elevate her to the condition of “voz da América Latina”? The main aim of the thesis is to study the discursive elaboration of Mercedes Sosa's life in biographical documentaries in order to understand how this idea of the “voz da América Latina”, with the goal to contribute theoretically to a recent reflection about discourse in Bakhtinian studies. We unfold this main aim into three others specifics, what are, to characterize the biographical discourse, from a historical, epistemological and discursive point of view, producing an examination of its discursive functioning; to study the discursive elaboration of Mercedes Sosa's life as it is presented in the documentaries in analysis; discuss the meanings of the epithet “voz da América Latina” in the comparison between moments of emergence and permanence after the singer's death. The theoretical-methodological approach will be based mainly on the discussion of the authors of the Bakhtin Circle (BAKHTIN, 2011, 2015, MEDVIÉDEV, 2012, VOLÓCHINOV, 2017) on the meeting of discourses, through comparison, based on the notions of transmission, understanding and evaluation of the speech of the other. We organized the thesis in three parts. In part I, we characterize the biographical discourse and delimit the ways to understand it; in part II, we analyze fragments of chronologically organized documentaries and perceive the affirmation of conditioning elements for the epithet “a voz da América Latina”; in part III, we present the emergence and permanence of the epithet from an analysis of its meanings, we consider that this part contains the validating elements for Mercedes Sosa to be considered “a voz da América Latina”. Finally, we enunciate the thesis defended in this work: her voice, the militant content of the songs, the historical-political period, the previous life, the political struggle, the Latin American connection are ingredients in the discursive elaboration of Mercedes Sosa's life in the biographical documentaries and help to consolidate the edifying values related to the epithet “voz da América Latina”. The combination of these factors legitimizes that the name Mercedes Sosa is raised to the status of voice of the continent, once one considers the adherence of her singing profession – despite the other intellectuals and artists active at the same time – her vocal power, the questions that the repertoire presented and, above all, her political action.